A Case Report: Young Adult with Drug Treatment-Resistant Depression-Induced Suicide Attempt Successfully Treated with Electroconvulsive Therapy - Florencia Leona, Denada (Yayasan Literasi Sains Indonesia, 2023)
Major depressive disorder is a serious mental problem that negatively affects a person's emotions, mind, and actions. A suicide attempt is an attempt to end a life that does not end with death but self-harm. People with major depressive disorder are at the highest risk of suicide. This case study shows what can be seen in a suicide attempt patient with an underlying treatment-resistant major depressive disorder. We present a case of a young female with a treatment-resistant major depressive disorder that induces suicide attempts. We found that adultery, disability child, and poverty had triggered major depression in her. Her family history of suicidal attempts is suspected to be also related to her suicidal behavior. She had no response to medications but showed good improvement after being treated with ECT. Further studies are needed to understand better the association between major depression in young adults, suicidal behavior, and medication resistance.